Cholera Toxin Subunit B as Adjuvant––An Accelerator in Protective Immunity and a Break in Autoimmunity - Thomas Stratmann (Vaccines, 2015)
Cholera toxin subunit B (CTB) is the nontoxic portion of cholera toxin. Its affinity to the monosialotetrahexosylganglioside (GM1) that is broadly distributed in a variety of cell types including epithelial cells of the gut and antigen presenting cells, macrophages, dendritic cells, and B cells, allows its optimal access to the immune system. CTB can easily be expressed on its own in a variety of organisms, and several approaches can be used to couple it to antigens, either by genetic fusion or by chemical manipulation, leading to strongly enhanced immune responses to the antigens. In autoimmune diseases, CTB has the capacity to evoke regulatory responses and to thereby dampen autoimmune responses, in several but not all animal models. It remains to be seen whether the latter approach translates to success in the clinic, however, the versatility of CTB to manipulate immune responses in either direction makes this protein a promising adjuvant for vaccine development.